Advanced Oxidation Processes Based On Ozone As A Treatment Alternative For Landfill Leaches - Becerra-Moreno , Dorance; Rubio-Gomez , Yrany; Ramírez-Ríos, Luisa Fernanda; Barajas-Solano , Andrés Fernando; Machuca Martínez, Fiderman (Universidad Pedagógica y Tecnológica de Colombia, 2021)
Ozone-based processes are part of the Advanced Oxidation Processes that have been applied on leachates from landfills. The highly toxic characteristics of landfill leachates can be reduced by ozone-based processes, which have been shown to achieve high removals of pollutants, especially recalcitrant organic compounds. In this review, recent information is compiled (2015 to 2021) regarding ozone-based processes, where the efficacy as a treatment has been studied, the optimal conditions are analyzed according to the type of leachate and the treatment method to be used. The implementation trend is identified as pre-treatment and post-treatment coupled with conventional processes.